1981
DOI: 10.1111/j.1439-0434.1981.tb03371.x
|View full text |Cite
|
Sign up to set email alerts
|

Selective Induction Infection Cushions by Rhizoctonia solani Relation to Host Responses

Abstract: Stimulation of growth by Rhizoctonia solani with the formation of infection cushions as a response to root exudates was reported by many authors (KERR 1956, FLENTJE et al 1963, WYLUE 1959, DODMAN and FLENTJE 1970), In 1968 a correlation between the type of infection cushions formed by R. solani and the mode of fungal penetration into host tissues. They introduced evidence that induction of dome-shaped infection cushions was followed by a direct penetration with or without penetration pegs, while formation of l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

1985
1985
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 5 publications
(4 reference statements)
1
3
0
Order By: Relevance
“…Abundant literature suggests that infection cushion formation by R. solani is induced by host exudates (Dodman & Flentje, 1970;Marshall & Rush, 1980a;El-Samara et al, 1981), In our experiments we observed that more infection cushions were formed on collodion membranes placed over soybean leaves of susceptible than resistant cultivars. Only the isolates of AG-1 I A, IB, and IC formed infection cushions on collodion membranes placed over soybean leaves.…”
Section: Discussionsupporting
confidence: 53%
“…Abundant literature suggests that infection cushion formation by R. solani is induced by host exudates (Dodman & Flentje, 1970;Marshall & Rush, 1980a;El-Samara et al, 1981), In our experiments we observed that more infection cushions were formed on collodion membranes placed over soybean leaves of susceptible than resistant cultivars. Only the isolates of AG-1 I A, IB, and IC formed infection cushions on collodion membranes placed over soybean leaves.…”
Section: Discussionsupporting
confidence: 53%
“…Large infection cushions were formed by highly branched and agglomerated hyphae (Figure 1B). Additionally, smaller infection structures similar to lobate appressoria (Figure 1C) and foot structures (Figure 1D) were observed, as described for Rhizoctonia solani [40,42,43,51-53]. Trichothecenes are potent phytotoxins that can evoke symptoms like necrosis in a wide variety of plants at very low concentrations [7].…”
Section: Resultsmentioning
confidence: 96%
“…Additionally, the results exclude a dependence of compound appressoria formation on certain topographical features, because the epidermal architecture of bracts and caryopses is fundamentally different. Topographical features of the inoculated surface [ 40 ], the availability of nutrients [ 40 , 57 ] and plant exudates [ 40 , 43 , 57 - 59 ] were discussed to be influencing factors for development and morphology of compound appressoria from R. solani . Several abiotic factors which influence fungal growth and development, like humidity, temperature, exposure to light, and nutrient availability will probably influence the development of compound appressoria.…”
Section: Discussionmentioning
confidence: 99%
“…Penetration of the epidermis occurred after formation of appressorium-like structures and infection cushions. On roots of cabbage seedlings, no formation of infection structures was observed, possibly because the cuticle composition or the absence of specific root exudates did not induce infection structure formation [ 44 , 45 , 46 ]. On tomato seedlings S. cepivorum formed infection structures similar to those on onion seedlings, although they did not result in successful invasion of the tomato-root system.…”
Section: Discussionmentioning
confidence: 99%